![\frac{ \cos \: a}{1 + \sin \: a} + \: \frac{1 + \sin \: a }{ \cos \: a } \: = 2 \sec \: a \frac{ \cos \: a}{1 + \sin \: a} + \: \frac{1 + \sin \: a }{ \cos \: a } \: = 2 \sec \: a](https://tex.z-dn.net/?f=+%5Cfrac%7B+%5Ccos+%5C%3A+a%7D%7B1+%2B++%5Csin+%5C%3A+a%7D++%2B++%5C%3A++%5Cfrac%7B1+%2B++%5Csin+%5C%3A+a+%7D%7B+%5Ccos+%5C%3A+a+%7D+%5C%3A++%3D+2+%5Csec+%5C%3A+a)
![prove prove](https://tex.z-dn.net/?f=+prove+)
Answers
Answered by
15
Answer:
Please check the attached image for
Attachments:
![](https://hi-static.z-dn.net/files/d78/a6d7459ae542080e8ad9b3c5150ee865.jpg)
Anonymous:
Brother... Thanks a lot ..♥️
Answered by
15
Qᴜᴇsᴛɪᴏɴ :-
Prove :- cosA/(1+sinA) +(1+sinA)/cosA = 2secA
Sᴏʟᴜᴛɪᴏɴ :-
Taking LHS,
→ cosA/(1+sinA) +(1+sinA)/cosA
Adding By taking LCM of Denominator, we get,
→ {cosA*cosA + (1+sinA)*(1+sinA)} / {cosA(1+sinA)}
→ {cos²A + (1+sinA)²} / {cosA(1+sinA)}
Now, Using (a + b)² = a² + b² + 2ab in Numerator,
→ {cos²A + 1 + sin²A + 2sinA} / {cosA(1+sinA)}
→ {1+(sin²A + cos²A) + 2sinA} / {cosA(1+sinA)}
putting (sin²A + cos²A) = 1 Now,
→ { 1 + 1 + 2sinA} / {cosA(1+sinA)}
→ {2 + 2sinA} / {cosA(1+sinA)}
Taking 2 common from Numerator,
→ 2{ 1 + sinA } / {cosA(1+sinA)}
cancel (1 + sinA) from N & D,
→ 2/cosA
using (1/cosA) = secA in Last,
→ 2secA = RHS (Proved).
Similar questions
Math,
5 months ago
Computer Science,
5 months ago
English,
11 months ago
Science,
11 months ago
Environmental Sciences,
1 year ago